Strategies to improve historically disadvantaged university staff’s wellbeing and administration of academic programmes during COVID-19: A descriptive survey study - Makgahlela, M.; Mothiba, T.; Mphekgwana, P. M.; Makhado, L.; Selepe, M.; Mokwena, J. P. (South African Journal of Higher Education, 2021)
The coronavirus (COVID-19) pandemic has brought the world to a standstill, impacting negatively on human mortality and morbidity. Currently, most countries are on a national lockdown as a way of curbing the rapid spread of the virus. Although desirable, nationwide lockdown continues to hamper the smooth running of the government’s key strategic sectors including the schooling system. In this descriptive qualitative study, we explored university staff (n = 87; Meanage = 38.54; males = 50.6%, females = 49.4%) views on strategies that could improve their wellbeing and administration of academic programmes during-and-immediately after the COVID-19 national lockdown. Participants were sampled conveniently and responded to an open-ended questionnaire online. The participating staff recommended five key strategies that were thematically analysed, which are as follows: a) improved communication; b) provision of efficient ICT infrastructure; c) consideration of compensatory academic measures; d) on-campus COVID-19 risk management strategy; and e) provision of online and on-campus psychological services. Based on these findings, it is recommended that the historically disadvantaged universities should consider implementing strategies for enhancing the staff’s wellbeing and administration of academic activities. However, whether the suggested strategies could yield positive results, post-implementation evaluation research may be needed. For future preparedness, present findings imply that institutions of higher learning need to put in place contingency plans for efficient communication in times of crises similar to COVID-19 while investing in efficient ICT infrastructure for remote learning, teaching, and research.